Model of wireless transmission of biomedical parameters for the monitoring of patients in intensive care units (2015)
The present study aimed to design a model for monitoring and transmission of biomedical parameters basedon wireless technology. This responds to a latent need in terms of improving the efficiency of the operation of the intensive care units (ICU), so progress in wireless transmissions, provides an emerging alternative to the medical-care personnel can monitor the condition of a patient in that unit. The methodology corresponds to a Feasible Project, developed through five stages: a) analysis of the situation under study, b) characterization of biomedical signals, c) establishing requirements and transmission monitoring system, d) design model and, e) model evaluation. As a result the model monitoring and transmission of biomedical parameters based on wireless technology is presented. In addition, the study failed to prove its feasibility by simulation in MatLab Software, establishing in a virtual environment system transmitter performance, through the calculated parameters.